2023
DOI: 10.3390/fishes8050225
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mycobacterium chelonae from Lined Seahorse Hippocampus erectus and Histopathological Analysis

Abstract: The lined seahorse (Hippocampus erectus) is an aquacultural species in China and has important economic and ornamental value. However, the species is affected by disease, which restricts their large-scale cultivation. In 2021, a disease was observed in cultured seahorses in Tianjin, China, with a cumulative mortality rate of 20%. The symptoms observed in the moribund seahorse included a weak swimming capacity, discolored body surface, enlarged liver and kidneys, and numerous white nodules in the parenchymatous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In recent years, the formation of granulomas in visceral tissues has been reported in various marine and freshwater fish, such as turbot Scophthalmus maximus, half-smooth tongue sole Cynoglossus semilaevis Günther, seahorse Hippocampus erectus, and largemouth bass Micropterus salmoides [21][22][23][24][25]. Parasites, viruses, and bacteria have been identified as potential causes of nodules of internal organs in fish [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the formation of granulomas in visceral tissues has been reported in various marine and freshwater fish, such as turbot Scophthalmus maximus, half-smooth tongue sole Cynoglossus semilaevis Günther, seahorse Hippocampus erectus, and largemouth bass Micropterus salmoides [21][22][23][24][25]. Parasites, viruses, and bacteria have been identified as potential causes of nodules of internal organs in fish [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, no parasites or viral particles were observed in the tissues of diseased fish exhibiting nodular symptoms, ruling out the possibility of parasitic or viral infections. It has been reported that bacteria such as Mycobacterium spp., Nocardia seriolae, Renibacterium salmoninarum, Rickettsia spp., Francisella spp., Photobacterium damselae, Aeromonas schubertii, and Aeromonas salmonicida can cause nodules of internal organs in fish [21][22][23][24][25][28][29][30][31]. PCR detection of the first five pathogens was used in the current study, but yielded negative results.…”
Section: Discussionmentioning
confidence: 99%